CHARACTER OF ORANGE PEELS AS REDUCTION WATER POLLUTION - Sitti Nur Ilmiah; Lilik Erviani; Puji Setyorini (Jurnal Matematika dan Sains (JMS), 2022)
Environmental problems are important to overcame. This is related to the resulting problem. Pollutants can make natural conditions unbalanced. One of environmental problems is presence of water used for washing clothes. Alternative water pollution reduction need conducted with acidic conditions. Acidic conditions can be play a role as cleaner so conducted research with peels orange fermented. The aim of research is fin out character peels orange fermented as reducer clothes washing contamination. The research carry out to conducted character peels orange fermented as reducer clothes washing contamination. The research methods are descriptive qualitative and quantitative. This type of experimental research is used in this study. The result showed that character peels orange fermented was sour smell from peels orange dominant and brown orange color. The result of fermentation was pH (3.20) and temperature 30.2 ?C at T40. Pollutants clothes washing contamination test with peels orange fermented at T5 for pH and temperature respectively 4.14 and 33.5 ?C.